The gastrointestinal tract and Parkinson’s disease - Higinbotham, Alissa S.; Kilbane, Camilla W. (Frontiers in Cellular and Infection Microbiology, 2024)
Parkinson's disease (PD) is the second most common (De Lau and Breteler, 2006) and the most rapidly rising neurodegenerative disease in the world (GBD 2016 Parkinson's disease collaborators, 2018); the population of patients living with PD is expected to double over the next twenty years (Dorsey et al., 2018). The rising incidence and prevalence of PD is not fully understood, but factors such as prolonged survival, reduced rates of smoking, and exposures to environmental pollutants and toxins likely contribute (Bloem et al., 2021).The pathological hallmark of idiopathic PD is the Lewy body, a neuronal inclusion largely composed of aggregated alpha synuclein in the substantia nigra pars compacta dopaminergic neurons and other brain regions (Koga et al., 2021). Clinically, PD is characterized by bradykinesia plus resting tremor, rigidity, and/or postural instability according to the United Kingdom Parkinson's Disease Society Brain Bank criteria (Gibb and Lees, 1988). PD is preceded by a prodromal period that is often associated with the development of "non-motor symptoms" (Table 1). Non-motor symptoms include hyposmia, sleep disorders, such as rapid eye movement (REM) sleep behavior disorder, mood changes, autonomic nervous system involvement, pain syndromes, and cognitive changes (Kalia and Lang, 2015). While both motor and non-motor symptoms contribute to disability, the negative impact on perceived quality of life was found to be larger for the non-motor symptoms of PD (Santos-Garcia and de la Fuente-Fernandez, 2013).